2013
DOI: 10.1016/j.jtcvs.2013.07.075
|View full text |Cite
|
Sign up to set email alerts
|

Sternal force distribution during median sternotomy retraction

Abstract: The shape of sternal retractors considerably influences the force distribution on the sternal incision. In the SSR, forces on the cranial and caudal sternum are significantly higher than in the median section, whereas in the CSR, forces in the median section are highest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Median sternotomy is reported as the preferred surgical approach to explore the thoracic cavity, 1,2 especially in case of pyothorax. In human medicine, this surgery is reported to be associated with significant postoperative pain caused by tissue injury at the level of the skin, subcutaneous tissues, bone, and cartilage 3 . Sternal retractors are frequently used during surgery and produce disruptive forces, not only around the surgical site itself, but also at the costovertebral joints and more distant sites, due to rib fractures at the level of costovertebral joints, costochondritis, rib joint dislocation or nerve injury 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Median sternotomy is reported as the preferred surgical approach to explore the thoracic cavity, 1,2 especially in case of pyothorax. In human medicine, this surgery is reported to be associated with significant postoperative pain caused by tissue injury at the level of the skin, subcutaneous tissues, bone, and cartilage 3 . Sternal retractors are frequently used during surgery and produce disruptive forces, not only around the surgical site itself, but also at the costovertebral joints and more distant sites, due to rib fractures at the level of costovertebral joints, costochondritis, rib joint dislocation or nerve injury 3 …”
Section: Introductionmentioning
confidence: 99%
“…In human medicine, this surgery is reported to be associated with significant postoperative pain caused by tissue injury at the level of the skin, subcutaneous tissues, bone, and cartilage. 3 Sternal retractors are frequently used during surgery and produce disruptive forces, not only around the surgical site itself, but also at the costovertebral joints and more distant sites, due to rib fractures at the level of costovertebral joints, costochondritis, rib joint dislocation or nerve injury. 3 Different strategies have been reported in both human and veterinary medicine to treat perioperative pain associated with thoracic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite 75 years of widespread use, mechanical analyses of Finochietto-style retractors and biomechanical studies of thoracic retraction are virtually nonexistent in the literature, despite the trauma which it generates. It is widely accepted that slower retractions are less traumatic [4, 18, 22], and recently published sternotomy retraction results using dummies and human cadavers have demonstrated that forces applied to hemisternum can reach 350 N (Aigner et al [23] and Saggio et al [24]). Bolotin et al [25–27], using a novel instrumented retractor, published measurements of forces during retraction in a sheep model and, importantly, demonstrated that force monitoring can reduce tissue trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Sternal wound healing still occurs in 0.4-7% of all cases (1,2). In order to prevent wound healing complications, mechanical forces on the sternum should be distributed evenly, while achieving optimal surgical sight for the performed procedure (3,4). Here, we present a novel sternal retractor offering a wide range of uses ranging from minimally invasive upper sternotomy approaches to full sternotomy during complex combined CABG and multi-valve procedures.…”
mentioning
confidence: 99%